Need for Intra-Commercial Regulations in Contracting Structure of Corporate Outsourcing Contracts in India - Leelesh Sundaram; Selva Muthu (Journal La Bisecoman, 2022)
In the ongoing pattern, it could be seen that the corporate companies have now started to outsource their services and products to other budding companies who are not exclusively dedicated for the reason for doing outsourced work and then again it could be licitly discovered that companies or organizations to do exclusively outsourced work is also growing. In this point the companies' quality policies and assets have a been varying. Thus, a natural dissatisfaction arises to either of the company and an ambiguity arises concerning the possession merchandise that are purchased for the motivation behind doing an outsourced work. In this way an inquiry arises as to whether there should a need for recognition of quality policies and assets in the outsourcing contract of corporate companies as it could be noted that cooperate companies outsource their product oriented and service oriented works at a larger extent and as result an ambiguity pertains as to whether there is a need for changes in contracting structure of corporate outsourcing contracts in India. When this issue is studied on a global context is studied, it can be figured out that an aspect of economic regulation, more particularly, intra-commercial regulations solve the issue. Thus this study is carried out on the same aim.